2017
DOI: 10.1007/s00520-017-3685-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of methodologies, endpoints, and outcome measures in randomized trials of radiation therapy-induced nausea and vomiting

Abstract: Methodologies, endpoints, and outcome measures varied considerably among 34 randomized trials in RINV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Unfortunately, this is not always done. A systematic review of 34 phase III RINV trials showed that no trials reported their operational definition of nausea [7]. Most of our patients strongly agreed or agreed with the provided MASCC definition of nausea so it seems reasonable to use this moving forward.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Unfortunately, this is not always done. A systematic review of 34 phase III RINV trials showed that no trials reported their operational definition of nausea [7]. Most of our patients strongly agreed or agreed with the provided MASCC definition of nausea so it seems reasonable to use this moving forward.…”
Section: Discussionmentioning
confidence: 68%
“…Although it is more common to see qualitative grading scales for nausea in antiemetic clinical trials [7], our patients preferred an ordinal scale. It may be that they were influenced by their familiarity with this type of scale, however.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations